City, Nature and Environmental Knowledge - Ángel, Felipe (2010)
That´s to say a few notions: first, the very spirit of our days denies to the city the “citizenship” in nature. Well, if human genome is more than a hint, then we happily nourish its consequences: we are part of evolution. So in Mother Earth cohabitate two different rhythms: one human and another ecosistemic. Humans are part of nature but not of the ecosystem. We specify ourselves as a species by the fact of not having a niches. Cities rhythm imposes itself to a vast majority of the planet. The clash between these two rhythms, the city and the ecosystem, is the cause of actual environmental crises. Second, the relation between the city and the ecosystem is domestication, which consists in a methodic interruption of the ecosystems ways of functioning. A few examples: photosynthetic flows of energy sink in the entropic urban sickness; they never get back to flow as they used to. Food chains are decapitated by agriculture or by “cows” protected from transmitting its energy to the candid anxiety of a carnivorous; protected by law, by epistemological claws, by ferry tails, by technological devises, etc. Third, the city is cause rather than consequence. Cause of individual moods, of the boundries of what is philosophical , of archetypical loneliness felt by that species ashamed of its natural origin, of the inclination in the technological development, etc.; now days we are theconsequence of the city, not its cause. But there´s another path for the relation between the city and the ecosystem; we call biocity to the permanent challenge to achieve a sustainable interpretation of natures music with all of its orchestra playing the same rhythm.